Putative Key Role of Inositol Messengers in Endothelial Cells in Preeclampsia - Sirilaksana Kunjara; Patricia McLean; Laurens Rademacher; Thomas W. Rademacher; Fabiana Fascilla; Stefano Bettocchi; Marco Scioscia (International Journal of Endocrinology)
Immunological alterations, endothelial dysfunction, and insulin resistance characterize preeclampsia. Endothelial cells hold the key role in the pathogenesis of this disease. The signaling pathways mediating these biological abnormalities converge on PKB/Akt, an intracellular kinase regulating cell survival, proliferation, and metabolism. Inositol second messengers are involved in metabolic and cell signaling pathways and are highly expressed during preeclampsia. Intracellular action of these molecules is deeply affected by zinc, manganese, and calcium. To evaluate the pathophysiological significance, we present the response of the intracellular pathways of inositol phosphoglycans involved in cellular metabolism and propose a link with the disease.